2016
DOI: 10.1038/srep25901
|View full text |Cite
|
Sign up to set email alerts
|

The enzymes LSD1 and Set1A cooperate with the viral protein HBx to establish an active hepatitis B viral chromatin state

Abstract: With about 350 million people chronically infected around the world hepatitis B is a major health problem. Template for progeny HBV synthesis is the viral genome, organized as a minichromosome (cccDNA) inside the hepatocyte nucleus. How viral cccDNA gene expression is regulated by its chromatin structure; more importantly, how the modulation of this structure impacts on viral gene expression remains elusive. Here, we found that the enzyme SetDB1 contributes to setting up a repressed cccDNA chromatin state. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…We showed here that Cfp1 depletion in the host cell correlates with both the decrease of HBV transcription and H3K4me3 deposition on the cccDNA, suggesting that Cfp1 is necessary for the recruitment of Set1 to the viral DNA so it can be properly transcribed as has been already demonstrated for cellular CGIs 23 . This is further supported by data showing that cccDNA transcription is controlled by Set1 recruitment 24 . As for the Ad5 genome, it preferentially repositions at TSS and enhancers, suggesting that this virus may also exploits some local molecular TFs to promote its own transcription.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We showed here that Cfp1 depletion in the host cell correlates with both the decrease of HBV transcription and H3K4me3 deposition on the cccDNA, suggesting that Cfp1 is necessary for the recruitment of Set1 to the viral DNA so it can be properly transcribed as has been already demonstrated for cellular CGIs 23 . This is further supported by data showing that cccDNA transcription is controlled by Set1 recruitment 24 . As for the Ad5 genome, it preferentially repositions at TSS and enhancers, suggesting that this virus may also exploits some local molecular TFs to promote its own transcription.…”
Section: Discussionsupporting
confidence: 61%
“…The cellular factor CXXC finger protein 1 (CXXC1 or Cfp1) binds to non-methylated CGIs, establishing an active chromatin state in part through the recruitment of the methyltransferase Set1 responsible for H3K4me3 deposition 22 , 23 . Interestingly, DNA methylation as well as Set1-mediated H3K4 methylation of the viral cccDNA influence HBV transcription 24 26 . We silenced Cfp1 in HepG2-NTCP cells previously infected with HBV, as confirmed by RT-qPCR and western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it seems very likely that there will be further studies on the role of the HBV protein HBx which appears to function as an epigenetic regulator to dysregulate a number of cellular genes as well as regulate the virus (reviewed in [ 62 ]). HBx appears to dysregulate a number of cellular pathways in part by binding to genomic DNA [ 63 ], changing expression patterns of miRNAs [ 64 ], affecting histone methyltransferases [ 65 ], binding to SIRT1 to activate transcription [ 66 ], and cooperating with histone methylases and demethylases to change the cell expression pattern [ 67 ].…”
Section: Hepatitis Bmentioning
confidence: 99%
“…CHIP analyses indicated that HBx was recruited to the cccDNA minichromosomes and recruiting epigenetic modifiers to set up a transcription permissive cccDNA epigenetic status altered cccDNA-associated histone modification 77, 79, 80 . Specifically, HBx had been shown to promote cccDNA-associated histone acetylation as well as recruit histone lysine demethylase-1 (LSD1) to relieved SETDB1-mediated H3K9me3 and HP1 induced condensation of cccDNA minichromosomes 77 .…”
Section: Eradication or Functional Inactivation Of Cccdna Is Essenmentioning
confidence: 99%